2004
DOI: 10.2337/diabetes.53.suppl_3.s39
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Integrated Therapy of Type 2 Diabetes

Abstract: The macro-and microvascular burden of type 2 diabetes is well established. A number of recent single risk factor intervention trials targeting hyperglycemia, dyslipidemia, hypertension, procoagulation, microalbumuria, and existing cardiovascular disorders have, however, shown major beneficial effects on long-term outcome. The results from these studies are anticipated to change the future management of type 2 diabetes, and most of the updated national guidelines for the treatment of type 2 diabetes recommend a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 60 publications
0
54
0
6
Order By: Relevance
“…8 The subgroup of patients with albuminuria at baseline was added here for comparison with the Steno study of patients with type 2 diabetes and albuminuria at baseline, which has reported a relative risk decrease of 67% for fatal CVD and 56% for total mortality after an intervention period achieving superior effect on risk factors with intensive treatment, regarding HbA1c, total and LDL cholesterol, SBP and rate of urine albumin excretion. 6,7 Comparatively, the combined decrease in HbA1c, SBP and non-HDL:HDL achieved in Group 4 of our patients with albuminuria was associated with a relative risk reduction of around 57% (p = 0.002) for fatal CVD and 49% (p < 0.001) for total mortality, compared to our reference Group 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 The subgroup of patients with albuminuria at baseline was added here for comparison with the Steno study of patients with type 2 diabetes and albuminuria at baseline, which has reported a relative risk decrease of 67% for fatal CVD and 56% for total mortality after an intervention period achieving superior effect on risk factors with intensive treatment, regarding HbA1c, total and LDL cholesterol, SBP and rate of urine albumin excretion. 6,7 Comparatively, the combined decrease in HbA1c, SBP and non-HDL:HDL achieved in Group 4 of our patients with albuminuria was associated with a relative risk reduction of around 57% (p = 0.002) for fatal CVD and 49% (p < 0.001) for total mortality, compared to our reference Group 1.…”
Section: Discussionmentioning
confidence: 99%
“…This observational study of change in relevant cardiovascular risk factors should be regarded as additional evidence and complement to findings in previous randomized trials in type 2 diabetes on the importance of intensive treatment of the individual risk factors glucose, blood pressure and blood lipids, 26,31,32 and also on the effect of combined treatment of these risk factors. [5][6][7] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Im Jahr 1972 lebten im früheren Bundesgebiet 55 Prozent der Bevölkerung mit Kindern unter 18 Jahren zusammen (68,5 Prozent mit ledigen Kindern ohne Altersbegrenzung 673 GEO behauptet, dass das Ticken der "Zeitbombe Demografie" noch von zu wenigen gehört würde und dass Bürgermeister beschönigend von "negativem Wachstum" und "Stadtentwicklung rückwärts" redeten. 674 Die deutsche Bevölkerungswissenschaft war nach der NS-Herrschaft zurück-haltend geworden, demografische Zustände zu bewerten. 675 Erst in den letzten Jahren ist diese Einstellung abgelöst worden durch eine pronatalistische Haltung, die heute an allen deutschen Lehrstühlen außer Rostock vertreten wird.…”
Section: Familien In Deutschlandunclassified